Validation Study of Physical Activity and Sedentary Behavior in African-American Men and Women. - Hicks, Jennifer; Adams-Campbell, Lucile L.; Lu, Jiachen; Mills, Mary; Dash, Chiranjeev (Journal of Racial & Ethnic Health Disparities, 2024)
Background: Self-reported data of physical activity are practical and inexpensive ways to collect data, although, subject to significant measurement errors. Most physical activity questionnaires used in the USA have been predominately validated among non-Hispanic White American populations with limited attention paid to the validity of the measures among racial/ethnic minorities. Additionally, there are limited studies that have evaluated factors related to over- and under-reporting errors linked to self-reported physical activity data, particularly among African Americans. The primary objectives of this study were to validate self-reported levels of physical activity and sedentary behavior among African-American men and women against objective measurements and to identify the factors related to under- and over-reporting. Methods: This study was a 7-day, cross-sectional study conducted on African-American men and women (n = 56) who were between 21–70 years of age. Participants were required to attend two study visits for the collection of self-reported and objective measurements of physical activity and sedentary behavior (VO2max, DEXA scan, anthropometrics, ActivPal accelerometer, resting metabolic rate (RMR) and International Physical Activity Questionnaire (IPAQ) questionnaire. Results: Overall, energy expenditure measured by ActivPal was 24.1 MET/hr/week whereas self-reported (IPAQ) energy expenditure was 52.66 MET/hr/week. Self-reported sedentary time was 40.37 h/week, whereas sedentary time measured by ActivPal was 63.03 h/week. Obese participants tended to over-report their physical activity levels more so than non-obese participants (Obese, Activpal—23.89 MET/hr/week vs IPAQ—58.98 MET/hr/week; Non-obese, Activpal – 24.48 MET/hr/week vs IPAQ – 42.55 MET/hr/week). Both obese and non-obese participants underestimated their sedentary time (Obese, Activpal – 66.89 h/week vs IPAQ—43.92 h/week; Non-obese, Activpal -56.07 h/week vs IPAQ – 33.98 h/week). Conclusions: The results of this study found that the ActivPal validated physical activity and sedentary behavior among African-Americans. Self-reported data were found to be highly variable, whereas the objective assessments of physical activity and sedentary behavior had limited variability. It was also found that obese individuals over-estimated their self-reported physical activity levels and under-estimated sedentary behavior in comparison to the ActivPal. These findings strongly support the need to measure physical activity and sedentary behaviors objectively, particularly among African-Americans.